Proyectos empresariales en los Caños del Peral a principios del siglo XIX - Romero Peña, María Mercedes (Dicenda. Estudios de lengua y literatura españolas, 2008)
In this article, we gather all the information found in Madrid’s archives (Local Files, Palace General Files, National Historic Files), dealing with the employers’ organization of the Madrid Theatre of «Los Caños del Peral» between the year 1800 and 1814. We explain what were the changes in management and government in this «Coliseo» as well as transcribe the main business projects during the lustrums at the beginning of the Century.